Kolaborasi Mahasiswa KKN dan Posyandu Dalam Meningkatkan Kesadaran Gizi Masyarakat di Kabupaten Jember - Masrifatul Roidha; Alfi Aulia Majid; Eka Sulistya Anggraeni; Tsaqif Fadhlilhaq; Holisatul Amalia; Fiorentina Amanda Argawandani; Meylaffena Fernanda; Jessica Maylaffazyza; Virginia Mandasari (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to examine the collaboration between KKN students and Posyandu in increasing public nutrition awareness in Jember Regency. Using qualitative descriptive methods, data were collected through participatory observation, in-depth interviews, and documentation studies. The results showed that collaboration was realized in the form of monthly Posyandu activities, nutrition education classes, and home visits. There was an increase in public nutrition awareness as indicated by increased attendance at Posyandu, positive changes in family eating patterns, and increased nutritional knowledge scores. The main challenges include limited time and resources, but can be overcome through careful program planning and collaboration with the local government. Long-term impacts are seen from the increased capacity of Posyandu cadres and the formation of sustainable networks. This study concludes that the collaboration between KKN  students and Posyandu is effective in increasing public nutrition awareness, emphasizing the importance of multi-party cooperation in public health programs.